2019
DOI: 10.3390/su11236536
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ethical Marketing Issues in Consumer-Brand Relationship

Abstract: This study investigated the components of ethical marketing such as product, price, place, and promotion using ethical views on the consumer-brand relationship and perceived product quality in B2C (business to consumer) transactions. It examined whether the quality and consumer-perceived product quality of a consumer-brand relationship affects corporate brand loyalty. Data from a panel of 1,200 consumers who had multiple experiences with a company’s products and brands were used to test the hypotheses, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 81 publications
2
23
1
2
Order By: Relevance
“…But, unfortunately most organizations define minimum acceptable ethical behavior and implement this level" (Caner & Banu, 2014). Lee and Jin (2019) confirmed that "To build a relationship with the consumer, the company should hone authentic communication. When truthful and accurate information about a product, such as its price through advertising, is communicated, the consumer is likely to exhibit high trustworthiness in the corporation and its brand."…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…But, unfortunately most organizations define minimum acceptable ethical behavior and implement this level" (Caner & Banu, 2014). Lee and Jin (2019) confirmed that "To build a relationship with the consumer, the company should hone authentic communication. When truthful and accurate information about a product, such as its price through advertising, is communicated, the consumer is likely to exhibit high trustworthiness in the corporation and its brand."…”
Section: Literature Reviewmentioning
confidence: 99%
“…Communicating "truthful and accurate information about a product" a company can make the customer loyal to its brand. Lee and Jin (2019) stated that "Factors such as advertising under legal legislation and degree of misleading or deceptive aspects are thus critical when building a strong relationship with the brand; they also improve product quality. "…”
Section: Ethical Norms and Valuesmentioning
confidence: 99%
“…This study found that most SME players in Makassar City only focus on selling and have not thought about the quality of their product brands. The components of ethical marketing include product, price, place, and promotion with an ethical consideration of the brand-consumer relationship and perceived product quality in a transaction [136]. Seventh, the SMEs in Makassar City have not been able to implement customer loyalty programs, in this case, related to member registration, customer communities, and regular promotions.…”
Section: Determinants Of Human Resource Capacity and Productivity Of Smesmentioning
confidence: 99%
“…According to the American Marketing Association, marketing is "an organizational function and a set of processes for creating, communicating and delivering value to consumers and managing this relationship in ways that benefits the organization and its stakeholders" (Lee & Jin, 2019). Also, marketing refers to all activities that take goods and products from the place of processing and production to the place of sale or consumption.…”
Section: Goals Of the Users And Retailers Via Product Designmentioning
confidence: 99%
“…The ergonomic value requires product compatibility with consumers' capabilities and the human body's measurements (Lee & Jin, 2019). Usage functions can be implemented in a product at a high or low easiness of use.…”
Section: The Ergonomic Valuementioning
confidence: 99%